2004
DOI: 10.1021/jf040188w
|View full text |Cite
|
Sign up to set email alerts
|

Linolenic Acid-Modified Chitosan for Formation of Self-Assembled Nanoparticles

Abstract: Chitosan was modified by coupling with linolenic acid through the 1-ethyl-3-(3-dimethylaminopropyyl)carbodiimide-mediated reaction. The degree of substitution was measured by 1H NMR, and it was 1.8%, i.e., 1.8 linolenic acids group per 100 anhydroglucose units. The critical aggregation concentration (CAC) of the self-aggregate of hydrophobically modified chitosan was determined by measuring the fluorescence intensity of the pyrene as a fluorescent probe. The CAC value in phosphate-buffered saline (PBS) solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 31 publications
1
86
3
Order By: Relevance
“…The increased stability could maintain activity of Dox to have interaction with topoisomerase II to form DNA-cleavable complexes and produce cytocidal activity, and this prolonged stability could be crucial to extending the therapeutic effect in vivo. 36 Notably, the body weight of mice decreased significantly during the treatment period for the SPIO-PEG-D group as shown in Figure 12B, while there was no significant change for the SPIO-PEG-D/ MF group. The results demonstrated that SPIO-PEG-D/MF can enhance the tumor treatment and reduce the drug toxicity to provide a safer nanodrug delivery.…”
Section: In Vivo Mr Imaging and Detection Of Ironmentioning
confidence: 92%
“…The increased stability could maintain activity of Dox to have interaction with topoisomerase II to form DNA-cleavable complexes and produce cytocidal activity, and this prolonged stability could be crucial to extending the therapeutic effect in vivo. 36 Notably, the body weight of mice decreased significantly during the treatment period for the SPIO-PEG-D group as shown in Figure 12B, while there was no significant change for the SPIO-PEG-D/ MF group. The results demonstrated that SPIO-PEG-D/MF can enhance the tumor treatment and reduce the drug toxicity to provide a safer nanodrug delivery.…”
Section: In Vivo Mr Imaging and Detection Of Ironmentioning
confidence: 92%
“…The samples were prepared by deionized water and placed on copper grids. Then copper grids were negative stained by 1% (w/v) phosphotungstic acid and were air-dried at room temperature before observation [27].…”
Section: Particle Size Of Blank and Drug-loadedmentioning
confidence: 99%
“…Tan and coworkers [64,65] prepared doxorubicin-loaded folate (FA)-modified carboxymethyl chitosan (FCC) hydrogel nanoparticles which were used as a FA-receptor-targeted drug carrier for tumor-specific drug delivery. Cellular uptake of FCC nanoparticles was found to be higher than that of nanoparticles based on linoleic acid (LA)-modified carboxymethyl chitosan because of the FA-receptor-mediated cellular uptake, thereby providing higher cytotoxicity against HeLa cells.…”
Section: Systemic Versus Localized Drug Delivery Systemsmentioning
confidence: 99%